2016
DOI: 10.1016/j.pmrj.2016.07.534
|View full text |Cite
|
Sign up to set email alerts
|

Powered Exoskeletons for Walking Assistance in Persons with Central Nervous System Injuries: A Narrative Review

Abstract: Individuals with central nervous system injuries are a large and apparently rapidly expanding population-as suggested by 2013 statistics from the American Heart Association. Increasing survival rates and lifespans emphasize the need to improve the quality of life for this population. In persons with central nervous system injuries, mobility limitations are among the most important factors contributing to reduced life satisfaction. Decreased mobility and subsequently reduced overall activity levels also contrib… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
76
0
5

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
4
1

Relationship

0
10

Authors

Journals

citations
Cited by 141 publications
(81 citation statements)
references
References 46 publications
0
76
0
5
Order By: Relevance
“…Reviews about robotic rehabilitation for gait recovery in stroke patients mainly involved static exoskeletons [22]; reviews about wearable powered exoskeletons are few, with small populations, and are mainly technical, scoping, or narrative [23,24].…”
Section: Resultsmentioning
confidence: 99%
“…Reviews about robotic rehabilitation for gait recovery in stroke patients mainly involved static exoskeletons [22]; reviews about wearable powered exoskeletons are few, with small populations, and are mainly technical, scoping, or narrative [23,24].…”
Section: Resultsmentioning
confidence: 99%
“…However, they remain as the less desirable options due to the lack of upright bipedal walking. It has been suggested that standing itself has physical and psychological benefits that are not replicated by wheelchairs (Esquenazi et al 2017). …”
Section: Non-orthotic Robot-based Hybrid Systemsmentioning
confidence: 99%
“…Es por ello que en los últimos años han surgido exoesqueletos y sistemas robóticos que pretenden rehabilitar a pacientes con marcha hemiparética. Debido a la naturaleza de esta patología, podemos encontrar tanto dispositivos bilaterales para terapia sobre suelo [11], como por ejemplo Ekso [12], Exo-H2 [13] o Hal-3 [14], o dispositivos montados sobre cinta rodante tales como Lokomat [15] o Lopes [16]; así como sistemas unilaterales [17] o monoarticulares [18], [19].…”
Section: Introductionunclassified